2006
DOI: 10.1177/002214650604700302
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Origins of the Race Gap in Men's Mortality

Abstract: Using a life course framework, we examine the early life origins of the race gap in men's all-cause mortality. Using the National Longitudinal Survey of Older Men (1966-1990), we evaluate major social pathways by which early life conditions differentiate the mortality experiences of blacks and whites. Our findings indicate that early life socioeconomic conditions, particularly parental occupation and family structure, explain part of the race gap in mortality. Black men's higher rates of death are associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(126 citation statements)
references
References 62 publications
6
120
0
Order By: Relevance
“…In order to lessen people's lifetime accruals of events and chronic hardships, policies would need to target "upstream" macro-level structural inequalities in addition to "downstream" stress-buffering resources possessed by individuals. Stress researchers and cumulative advantage/disadvantage investigators converged on a fundamental policy conclusion (e.g., Aneshensel 2009;Cooksey et al 1997;Geronimus 1992;House 2002;House et al 1988House et al , 1994Link and Phelan 1995;Turner and Avison 2003;Umberson et al 2005;Walsemann et al 2008;Warner and Hayward 2006;Williams et al 1997):…”
Section: Policy Implication 1: To Reduce the Health Impacts Of Major mentioning
confidence: 99%
“…In order to lessen people's lifetime accruals of events and chronic hardships, policies would need to target "upstream" macro-level structural inequalities in addition to "downstream" stress-buffering resources possessed by individuals. Stress researchers and cumulative advantage/disadvantage investigators converged on a fundamental policy conclusion (e.g., Aneshensel 2009;Cooksey et al 1997;Geronimus 1992;House 2002;House et al 1988House et al , 1994Link and Phelan 1995;Turner and Avison 2003;Umberson et al 2005;Walsemann et al 2008;Warner and Hayward 2006;Williams et al 1997):…”
Section: Policy Implication 1: To Reduce the Health Impacts Of Major mentioning
confidence: 99%
“…Minority men's health outcomes are the result of dynamic notions of manhood and gendered and non-gendered determinants of health. The field of minority men's health would benefit from critical examination of the contributions of critical periods and life transitions, 86 educational and other pathways, 68 and the cumulative effect of disadvantage and gendered racism 13 over time. Research and policies to improve minority men's health should recognize and address the psychological, health and social consequences of not being able to marshal the material resources necessary to express normative or hegemonic masculinities while we help men develop more progressive notions of manhood.…”
Section: Manhood and Minority Men's Health -Griffithmentioning
confidence: 99%
“…Recent studies have reported that persons with traumatic events, low SES, or poor health during childhood are at increased risk of morbidity and mortality as adults (Barnes et al, 2012;Montez et al, 2013;Warner & Hayward, 2006;Hayward & Gorman, 2004;Banks et al, 2011;Blackwell et al, 2001). Some plausible non-stress pathways which might also contribute to differential gene expression include increased drinking and smoking as well as higher rates of obesity-by individuals who face significant or chronic adversity (Anda et al, 2010).…”
Section: Hhs Public Accessmentioning
confidence: 99%